Stress and burnout among first year undergraduate medical students of a private medical college: a cross-sectional study - Akham, Ngamba; Goutam, Soram; Gambhir Singh, Toijam (International Journal Of Community Medicine And Public Health, 2023)
Background: Stress can be considered as a double-edged sword. Various studies have provided evidence of stress amongst medical students. There have been no studies regarding prevalence of various stress factors among the medical students of the only private medical college in Manipur. Methods: A cross-sectional study was conducted at Shija Academy of Health Sciences, Langol amongst the first MBBS Batch 2022. Convenience sampling method was adopted. medical students stress questionnaire was used for assessing Stress and Maslach burnout inventory-student survey was used for assessing Burnout of the medical students. Results: A total of 148 medical students participated. For stress predictor domains, the academic related stressor was found to have the highest mean score (2.30±0.65). There were statistically significant associations between the social related stressor score with location of home of students and academic related stressor with self-graded academic performance. There was also significant association between group activities related stressor and self-graded academic performance of students. for burnout domains, the employment/occupational exhaustion had the highest mean score (26.54±9.37). Statistically significant associations were found between depersonalization with gender and location of home of students, and occupational exhaustion with self-graded academic performance of students. Conclusions: This study reveals the need for stress management modules development for students with special focus on academic and social related stressors.